Vpliv vadbe za vzdržljivost na upad pozornosti pri starejših odraslih - Koščak Tivadar, Blanka (Šport (Ljubljana), 2024)
In the study, we examined whether an experimental intervention could influence the decline in attention in older adults. The experiment involved 80 elderly participants who were randomly assigned to three experimental groups, which performed endurance exercise, cognitive training, or a combination of both exercises three times a week for twelve weeks, and a control, fourth group. As a form of endurance exercise, we chose treadmill walking to avoid the influence of external factors that could affect task performance. In the context of cognitive training, participants performed memory, concentration, and mental exercises, which we adapted from published manuals. To verify the results, we used the Stroop test to assess selective attention. The study found a positive impact of endurance exercise on attention, where participants improved the inhibition of irrelevant stimuli. The results of the study confirm that proactive action, including appropriate physical exercise, is necessary for quality aging.
Keywords: active aging; aging; aktivno staranje; attention; cognitive exercise; elderly; endurance exercise; kognitivna vadba; older adults; pozornost; sport; staranje; starejši odrasli; starostnik; šport; vadba za vzdržljivost